2013
DOI: 10.1088/0960-1317/23/4/045014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of buckling transition from straight-sided to telephone-cord wrinkles in Al films

Abstract: Aluminum films 150 nm thick have been deposited on polymethylmethacrylate (PMMA) substrates by a magnetron sputtering process. Parallel straight-sided wrinkles are induced by axial compression. The evolution from straight-sided to ‘telephone-cord’ wrinkles is experimentally investigated using optical microscopy. Finite element modeling of instability is introduced for analyzing the secondary bifurcation or buckling of straight-sided wrinkles. Imperfections based on a random combination of buckling eigenmodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Our nonlinear simulations of the telephone cord buckles show that the minimum energy with respect to λ/b is very shallow as the value of σ 0 /σ E increases. The results reported here demonstrate that the interface sliding leads to a noticeable wavelength dependent minimum energy state, which maybe is the reason for the wavelength variation in the telephone cord buckle observed in experiments [18,27].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our nonlinear simulations of the telephone cord buckles show that the minimum energy with respect to λ/b is very shallow as the value of σ 0 /σ E increases. The results reported here demonstrate that the interface sliding leads to a noticeable wavelength dependent minimum energy state, which maybe is the reason for the wavelength variation in the telephone cord buckle observed in experiments [18,27].…”
Section: Discussionsupporting
confidence: 56%
“…The wavelength variation in the telephone cord buckles has widely been reported in experiments [18,27]. Moon et al [18] found that there is no measured value of λ/b smaller than 1.9 and the fraction of the value of λ/b above 1.9 is as much 40%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, buckling has attracted much attention as a useful approach for surface pattern controlment and material property characterization, which arises when a relatively thick substrate‐supported thin layer undergoes an excessive compression. The compression generally originates from the mechanical constants mismatch between different layers, which can be utilized to create interesting topographical patterns such as straight‐sided wrinkles, telephone cord structures, and circular blisters . A range of different strategies have been explored to produce patterns in thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Thin film buckling studies are generally started with eigenvalue buckling estimates. In our work, imperfections based on the random combination of buckling eigenmodes are introduced in the FEM analyses to take into account the film buckling [31]. The next step of a typical buckling analysis is to perform a nonlinear calculation of large deformation analysis, and finally to investigate the patterns of buckled films which are caused by initial geometric imperfections.…”
Section: Imperfectionsmentioning
confidence: 99%